2010
DOI: 10.1016/j.jmb.2010.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Expression-System-Dependent Modulation of HIV-1 Envelope Glycoprotein Antigenicity and Immunogenicity

Abstract: Recombinant expression systems differ in the type of glycosylation they impart on expressed antigens such as the Human Immunodeficiency Virus Type-1 (HIV-1) envelope glycoproteins, potentially affecting their biological properties. We performed head-to-head antigenic, immunogenic and molecular profiling of two distantly-related Env surface (gp120) antigens produced in different systems: a) mammalian (293F) cells in the presence of kifunensine which impart only high mannose glycans; b) insect (Spodoptera frugip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 66 publications
5
75
1
Order By: Relevance
“…Glycan-specific antibody responses can be an attractive line of vaccine development, since some glycan-specific MAbs demonstrate great neutralizing breadth and potency (51,54). It has also been shown that glycan-binding antibodies can be induced by synthetic glycans (2,3,17,19,26,57) or HM-glycan on non-HIV-1 proteins (1, 25, 34, 35). Unfortunately, a glycan-binding antibody capable of neutralizing diverse strains of primary HIV-1 has yet to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Glycan-specific antibody responses can be an attractive line of vaccine development, since some glycan-specific MAbs demonstrate great neutralizing breadth and potency (51,54). It has also been shown that glycan-binding antibodies can be induced by synthetic glycans (2,3,17,19,26,57) or HM-glycan on non-HIV-1 proteins (1, 25, 34, 35). Unfortunately, a glycan-binding antibody capable of neutralizing diverse strains of primary HIV-1 has yet to be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…DNA electroporation. Genetic vaccines avoid a bias in the immune response imparted by the Ag production system (35), and DNA electroporation has been shown to favor the induction of immune responses with a Th1 phenotype (36). Nevertheless, the Env-specific humoral immune response induced by our vaccine was highly dominated by the Th2-associated IgG1 subclass (Fig.…”
Section: Subclass Distribution Of Hiv-1-specific Absmentioning
confidence: 90%
“…Glycan modifications on proteins undergo a series of glycan processing steps from the endoplasmic reticulum (ER) to the Golgi apparatus with a diverse array of glycan processing enzymes that compete for available substrate, resulting in multiple glycosylation patterns for each glycosylation site for a given protein and variation in glycosylation site occupancy (35,52,53). Moreover, protein glycosylation varies significantly across different cell types, cell states, tissues, and organisms (3,12,16,34,35,53,56,62). Despite these challenges, recent advances in proteomics have accelerated the pace of the development of efficient methods and technologies that can be tailored for the analysis of protein glycosylation (6,51,66).…”
mentioning
confidence: 99%
“…The types of glycans on recombinant viral Env are beginning to be characterized (5,34), and the carbohydrates on recombinantly expressed envelopes may not be fully representative of those glycans on virion Env spikes (15). Nonetheless, comparison of recombinant transmitted/founder and chronic HIV-1 Env glycosylation with new carbohydrate analysis technology is an important initial analysis, primarily because of the anticipated use of recombinant transmitted/founder Envs in human immunogenicity trials.…”
mentioning
confidence: 99%